Catalytic effect of boric acid in CO2 absorption (2018)
As a consequence of the accelerated industrial growth, the problem involved in the treatment of gases emitted into the atmosphere by the industrial sector, especially carbon dioxide, takes on greater relevance. Therefore, the development and exploration of new technologies for the capture of CO2 must always be under investigation. This study employed a pilot-scale absorption unit to investigate the capacity of the absorption of carbon dioxide using an aqueous solution of sodium hydroxide and boric acid as catalyst. The evaluated parameters included two different concentrations of absorbent, operating temperature, and the kinetic effect due to the presence of boric acid. The results showed that when the concentration of the absorbent was increased, the removal of CO2 is highly favored. Also, the kinetic effect was favored when the operating temperature was stepped up, and the presence of boric acid improves the CO2 kinetic rate.